2015
DOI: 10.1038/ng.3198
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of the genomes of marine mammals

Abstract: Marine mammals from different mammalian orders share several phenotypic traits adapted to the aquatic environment and are therefore a classic example of convergent evolution. To investigate convergent evolution at the genomic level, we sequenced and de novo assembled the genomes of three species of marine mammals (the killer whale, walrus and manatee) from three mammalian orders that share independently evolved phenotypic adaptations to a marine existence. Our comparative genomic analyses found that convergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
429
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(475 citation statements)
references
References 38 publications
(38 reference statements)
17
429
2
4
Order By: Relevance
“…Both studies found instances of homoplasy in genes with plausible links to their convergent phenotypes 26,27 . However, similar amounts of homoplasy were also detected between non-convergent species 26 . Further analyses showed that homoplasious substitutions between marine mammals were largely consistent with relaxed purifying selection 28 .…”
Section: Nature Ecology and Evolutionmentioning
confidence: 97%
See 2 more Smart Citations
“…Both studies found instances of homoplasy in genes with plausible links to their convergent phenotypes 26,27 . However, similar amounts of homoplasy were also detected between non-convergent species 26 . Further analyses showed that homoplasious substitutions between marine mammals were largely consistent with relaxed purifying selection 28 .…”
Section: Nature Ecology and Evolutionmentioning
confidence: 97%
“…Under this assumption, molecular convergence in orthologous loci is suggested be an important driver of phenotypic convergence 25 . Recent genome-wide studies have attempted to identify homoplasious amino acids in protein-coding genes, notably among several marine mammal lineages and among echolocating mammals 26,27 . Both studies found instances of homoplasy in genes with plausible links to their convergent phenotypes 26,27 .…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…With high-quality reference genomes, this can be studied at levels ranging from the nucleotide up to the chromosome. At the nucleotide level, one series of questions of growing interest relates to constrained sequence evolution, for example, whether specific nucleotides or amino acids are under convergent evolution in phylogenetically disparate taxa, as has been showcased with regard to the evolution of echolocation in bats and marine mammals (e.g., 65,161). At the larger scale, there is considerable focus today on evolutionary trajectories of autosomal and sex chromosomes (162), and in particular whether major evolutionary transitions accompany significant chromosome-scale rearrangements.…”
Section: Evolution Of Genome Architecturementioning
confidence: 99%
“…Furthermore, the most extreme difference in terms of counts of changes observed (between I and V) was between amino acids in the same physico-chemical category and at a site with low amino acid diversity across the lineages, and thus likely reflects exchangeability rather than adaptation. Using genomic data, more biological information on the genetic basis of habitat shifts could firstly be obtained through consideration of convergence and similarities in gene types under differential selection pressures between habitats (e.g., Foote et al 2015).…”
Section: Molecular Convergence In Coi Based On Habitatmentioning
confidence: 99%